P123 A retrospective cohort study of the long term effectiveness of smoking cessation counselling. (2nd December 2011) - Ling, A C; Elward, D D; Barry, S
Abstract : Introduction and Objectives: A regional smoking cessation counselling service provides one-to-one counselling with follow-up by telephone and appointments for up to 1 year. Previously, no long-term evaluations of such methods of smoking cessation have been conducted. This study aimed to establish how successful the service is 5–10 years following counselling. Method: Patients were interviewed by means of a telephone questionnaire. Their current smoking status was assessed and baseline data including previous smoking habits was recorded. The intervention group were patients who completed the programme and deemed non-smokers after 1 year. The control group were patients who were referred but failed to attend. Both groups were referred to the service between 2001 and 2005. Seventy-nine out of 202 patients were interviewed from the intervention group and 121 out of 752 patients from the control group were interviewed. Results: Of those previously attending the programme, 30.4% had relapsed. Of the 69.6% of participants remaining non-smokers, 85.5% had remained non-smokers throughout this follow-up period. Participants who did not attend were more likely to remain smokers (63.3%, p=<0.001, RR=2.08). Of those attending the programme, 70% reported using additional methods (eg, nicotine replacement therapy) to aid cessation. However, these individuals had a higher rate of relapse (36% vs 20%, p=0.080). Lower socio-economic status may also be linked to a higher relapse rate (p=0.075). Baseline statistics comparing the two cohorts revealed that patients from a lower socio-economic background were less likely to have successfully attended the programme (p=<0.001). Gender or number of pack years accumulated at the time of invitation were not significantly different between cohorts and patient age was similar (control=59 years, intervention=62 years). Median follow-up for both cohorts was 8 years. Conclusions: This unique 5–10 year follow-up indicates that smoking cessation counselling is achieving its aim of assisting the long-term cessation of patients attending the programme. However, patients requiring further interventions such as nicotine replacement therapy and those from lower socio-economic groups have been identified as requiring additional encouragement. This may indicate areas for improvement that smoking cessation programmes should consider.